Coercivity Modulation in Fe–Cu Pseudo‐Ordered Porous Thin Films Controlled by an Applied Voltage: A Sustainable, Energy‐Efficient Approach to Magnetoelectrically Driven Materials. Issue 8 (20th June 2018) - Dislaki, Evangelia; Robbennolt, Shauna; Campoy‐Quiles, Mariano; Nogués, Josep; Pellicer, Eva; Sort, Jordi
Abstract: Fe–Cu films with pseudo‐ordered, hierarchical porosity are prepared by a simple, two‐step procedure that combines colloidal templating (using sub‐micrometer‐sized polystyrene spheres) with electrodeposition. The porosity degree of these films, estimated by ellipsometry measurements, is as high as 65%. The resulting magnetic properties can be controlled at room temperature using an applied electric field generated through an electric double layer in an anhydrous electrolyte. This material shows a remarkable 25% voltage‐driven coercivity reduction upon application of negative voltages, with excellent reversibility when a positive voltage is applied, and a short recovery time. The pronounced reduction of coercivity is mainly ascribed to electrostatic charge accumulation at the surface of the porous alloy, which occurs over a large fraction of the electrodeposited material due to its high surface‐area‐to‐volume ratio. The emergence of a hierarchical porosity is found to be crucial because it promotes the infiltration of the electrolyte into the structure of the film. The observed effects make this material a promising candidate to boost energy efficiency in magnetoelectrically actuated devices. Abstract : Magnetoelectric effects are investigated in porous Fe–Cu films fabricated by electrodeposition and colloidal lithography. The magnetic properties are controlled in a reversible manner at room temperature using an applied electric field generated through an electric double layer. A coercivity reduction of up to 25% is achieved mainly due to electrostatic charge accumulation at the surface of the porous alloy.